Hiperisolamento, Solidão e Coronavírus: A Defensoria Pública de São Paulo e o Direito das Pessoas Presas ao Convívio Familiar - Santos, Gustavo Samuel Da Silva [UNESP]; Barbosa, Agnaldo De Sousa [UNESP] (Universidade Estadual de Londrina, 2024)
This article aimed to analyze the Public-interest Civil Action (ACP) promoted by the São Paulo Public Defender’s Office to guarantee people deprived of liberty in the state of São Paulo access to public telephones and virtual visits during the COVID-19 pandemic. The analysis was not restricted to considerations about legal strategies but sought to understand how the law was used and mobilized to construct public policies for people in prison. A qualitative documentary analysis of the initial request was carried out. It was found that the main mechanism for preventing the circulation of the coronavirus in São Paulo prisons was increasing the isolation of inmates. Protection, however, meant restricting further rights of prisoners and increasing their suffering, restricting access to material assistance and means of preventing torture. In the Public-interest Civil Action, it was noticed that the Public Defender’s Office sought to present itself as an institution that promotes human rights and in order to convince the Judiciary of the justice of its requests, demonstrated that other countries and states of the federation had already regulated virtual contacts between prisoners and their families. Furthermore, the action was useful in denouncing the lack of effective COVID prevention policies. Finally, it was concluded that the request, although rejected in court, was important in provoking the state government to face the problem.

O presente artigo visou analisar a Ação Civil Pública (ACP) promovida pela Defensoria Pública paulista para garantir às pessoas privadas de liberdade no Estado de São Paulo acesso a telefones públicos e visitas virtuais durante a pandemia da COVID-19. A análise não se restringiu a considerações sobre as estratégias jurídicas, mas buscou compreender como o direito foi usado e mobilizado para a construção de políticas públicas para as pessoas presas. Foi feita uma análise documental de caráter qualitativo do pedido inicial. Verificou-se que o principal mecanismo de prevenção à circulação do coronavírus nas prisões paulistas foi o aprofundamento do isolamento dos encarcerados. A proteção, no entanto, significava a restrição de mais direitos das pessoas presas e o aprofundamento de seu sofrimento, restringindo acesso à assistência material e meios de prevenir tortura. Na Ação Civil Pública, percebeu-se que a Defensoria buscou se apresentar como instituição promotora de direitos humanos e, para convencer o Judiciário da justeza de seus pedidos, demonstrou que outros países e estados da Federação já haviam regulado contatos virtuais entre presos e familiares. Ademais, a ação foi útil para denunciar a falta de políticas efetivas de prevenção à COVID. Por fim, concluiu-se que o pedido, muito embora rejeitado judicialmente, foi importante para provocar o governo estadual a enfrentar o problema.
Hyperisolation, Loneliness, and Coronavirus: São Paulo Public Defender’s Office and the Right of Incarcerated Individuals to Family Life
Keywords: public defense; pandemic; prisons; public policies; Defensoria Pública; pandemia; prisões; políticas públicas